Hematologic, Immunologic and Outcome Characteristics of Severe acute respiratory syndrome 2 (SARS-COV-2) among People Living with HIV in Eastern Uganda: A Retrospective Study - Otaala, Timothy; Opito, Ronald; Mugisha, Kenneth; Bakashaba, Baker; Watmon, Benedicto; Etolu, Wilson; Lubaale, Moses Yovani; Olupot-Olupot, Peter (medRxiv, 2025)
Globally People Living with HIV (PLWHIV) are prone to severe opportunistic infections with Coronavirus disease of 2019 (COVID-19) inclusive. Dual infection of HIV and COVID-19 could complicate the clinical outcomes of these patients. This study sought to determine hematologic, immunologic, virologic and outcome characteristics of people with HIV and COVID-19 co-infections in two Mbale and Soroti Regional Referral Hospitals in Eastern Uganda. A retrospective review of medical records of PLHIV and contracted COVID-19 virus was conducted in two large regional referral hospitals in Eastern Uganda using a data abstraction tool. Data was captured using Kobo collect toolbox, downloaded in Microsoft Excel and analyzed using STATA version 15.0. Descriptive statistics was reported as frequencies and proportions, while contingency and comparisons were done at the bivariate level analysis. The penalized logistic regression was conducted at multivariate level to establish the factors associated with COVID-19 severity among PLHIV. A total of 100 patient records had 38%(n=38) of individuals aged 40-50 years and 62%(n=62) females. Most patients (6 in 10) were peasants with 79%(n=79) having low-income levels. Other than HIV, 3 out of 10 patients had comorbidities. Also, 30 had haematological records, of which 9 (30%) had leucocytosis and 3, leucopoenia. Further, 67% had immunologic records, of which 22 (33%) had CD4 counts <200 cells/mm3. Only 22% of patients had viral load results, of which 8 (36) were unsuppressed. Nineteen percent (19/100) patients had severe COVID-19 and 14% (14/100) died. Socio-demographic factors significantly associated with severe COVID-19 outcomes were being male (P=0.026) and having other comorbidities (P<0.001). A significant proportion of PLHIV co-infected with COVID-19 had abnormal hematological and virological status possibly due to varying socio-demographic characteristics. Clinical outcomes of HIV and COVID-19 co-infection may therefore vary depending on an interplay between host factors, viral factors, and comorbidities.